Arbitration in Kazakhstan: current state and prospects (Journal of actual problems of jurisprudence, 2019)
The article discusses, questions regarding the development of jurisprudence on the application of the rules governing recourse tothe enforcement of arbitral awards and arbitral tribunals, the study of which has particularly high practical value.Keywords: court, arbitration, defendant, plaintiff.